G346(P) Paediatric hot clinics as an integrated learning tool. (24th May 2017) - Begley, R; Roughley, C; Banerjee, K
Abstract : Aim: At Queen's Hospital, over 600 children were seen in hot clinics in 2015, with most children being under 1 year of age. Almost 50% had no investigations and 40% required no further follow up. Most common issues were for feeding problems and developmental concerns. This highlighted a group of patients that could safely be cared for in the community and we wanted to explore ways we could achieve this and hopefully a better patient experience. Methods: Surveying GP's and GP trainees showed; 18% of qualified GPs weren't confident in dealing with children 73% felt they needed more paediatric training. 73% also reported problems with communication between primary and secondary care. There was a very mixed opinion on how further teaching could be delivered. 2/3 of Trainees gain formal paediatric training in their GP VTS. 65%–88%of Trainees felt that they would be willing to use study leave for Paediatric learning opportunities. Almost 60% preferred learning to be based in a hospital. More than 90% of trainees would be willing to engage in learning together clinics, integrating paediatric and GP care. Using this information we have utilised paediatric hot clinics as an integrated learning tool. All local GP VTS could access and book themselves into clinic slots, via online calendar. Participants attended a minimum of 3 clinics, write a case report, and complete a reflective log of patients seen. Participant feedback: Some reported feeling more confident in treating children after the project 100% would recommended the project to peers Particularly found it helpful in management of feeding issues Clinics only had 2–3 patients per list so limited learning. Suggestions for expanding project to include time in Paediatrics A and E Future plans: Open this learning opportunity to other VTS schemes in the area and also qualified GPs Run alongside 'learning together' clinics, for paediatric and GP trainees in the community Amalgamate case reports into a booklet and learning resource Invite participants to attend paediatric departmental teaching on day of clinic